Taxation and Budget Reform Commission (TBRC) Statutory Recommendation: Sales and Use Tax Exemption Review Committee - Rodney L. Clouser (EDIS)
A series of 16 fact sheets by Rodney L. Clouser, inform the public on issues related to statutory and constitutional proposals adopted by the Taxation and Budget Reform Commission (TBRC). Fact sheets FE733 through FE741 address statutory changes and fact sheets FE742 through FE748 address constitutional amendments. Published by the UF Department of Food and Resource Economics, July 2008.